Hubungan antara Kesadaran Orang Tua Tentang Perkembangan Bahasa Dengan Kemampuan Bahasa Ekspresif Pada Anak Usia Prasekolah di KB-TK Aisyiyah Al-Amin Surakarta - Vina Wibowo, Devriani; Gunawan, Gunawan (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Abstract Background: The development of language skills in children is divided into 2, one of which is expressive language skills. An expansive language ability is a person's ability to convey messages verbally or in writing. The development of children can be influenced due to the awareness of the closest people, especially parents. But in reality, there are still many parents who do not have awareness of their role in stimulating children's language from an early age. Awareness consists of 5 aspects including AWAREness namely, Attention, Wakefulness, Architecture, Recall of Knowledge and Emotive. Purpose: The purpose of this study was to determine the relationship between parents' awareness about language development and expressive language skills in preschool-age children in KB-TK Aisyiyah Al-Amin Surakarta. Methods: This research is a quantitative study using a Cross Sectional research design. The sample used was 30 respondents based on the general benchmark of